Promosi Jabatan, Mutasi, Dan Motivasi Berprestasi Sebagai Upaya Meningkatkan Prestasi Kerja Aparatur Sipil Negara - Subandi Subandi (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
As a public servant, a civil servant must demonstrate high work performance. High work performance is a form of evidence that the civil servants concerned can carry out the tasks carried out properly. Therefore, various personnel management policies have been pursued by the government in improving work performance, including mutation, promotion and motivation. The purpose of this study was to find out the influence of achievement motivation, mutation and promotion of work performance of civil servants. Specifically, this study aims to determine the effect of (1) achievement motivation on work performance; (2) mutation of work performance; (3) promotion of work performance; and (4) the significance of the influence of achievement motivation, mutation, and promotion of work performance of civil servants in the Regional Civil Service Agency of the City of Blitar. This study uses descriptive analysis method with a quantitative approach. The research sample used the entire population, namely all civil servants in the Regional Civil Service Agency of Blitar City were 35 people. Data obtained through instruments in the form of questionnaires with linkert scale. Data analysis using multiple linear regression. The results showed that (1) achievement motivation had a positive and significant effect on work performance. (2) mutations have a positive and significant effect on work performance. (3) job promotion does not have a positive and significant effect on work performance. (4) collectively achievement motivation, mutation and promotion have a significant effect on job performance.